Introducing Undergraduate Students to Nonlinear Dynamics through A Numerical Approach - Nugroho, Fahrudin; Azhari, Irfan Taufiq; Yusuf, Yusril; Nurwantoro, Pekik (Program Studi Pendidikan Fisika UHAMKA, 2018)
This paper describes a numerical method that used to solve the nonlinear Schr\